Histopathological and Heamatological Study in Experimentally Infected Rabbits with Leishmania tropica. - Al-Salih, Waddah Salam; Faraj, Azhar Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This study was conducted in the laboratories of the Department of Parasitology, Faculty of Veterinary Medicine, University of Baghdad, during the period from the beginning of February 2022 to the end of February 2023. Iraq is an endemic country with a high frequency of both types, visceral and cutaneous leishmaniasis, with several clinical manifestations. This study was designed to describe the histopathological alterations of skin infection and compare the hematological parameters between two groups of rabbits. In this study used two groups of rabbits one of which was experimentally infected with L. tropica. Leishmania tropica isolate was obtained from AL-Nahrain University, Biotechnology Research Center, isolated from human infection with cutaneous leishmaniasis, and identified by PCR technique. The histopathological study showed as follows: The first group (control group) shows normal skin tissue; there is a thin epidermis covered by a thick stratum corneum, and the dermis contains an eosinophilic network of collagen fibers, sweat glands, and hair follicles. The other section showed higher magnification, normal epidermal layers with a thick keratinized layer above the epidermis; however, in the second group (infected with L. tropica) there is incomplete healing of the epidermal layer except for a few hyperplasia of stratum basale and destruction of the keratinocyte layer. Few infiltrations of inflammatory cells, mainly macrophages and eosinophils, and there is no healing and complete separation of epidermal layers and destruction of hair follicles and sweat glands. Find an irregular collagen network; in Lymphocytes, WBCs, and platelets were all significantly affected by cutaneous Leishmania infection. The increase of granulation led to decreased the number of amastigote stages